CULTURAL VALUE ANALYSIS AT MADRASAH ALIYAH TAHFIDZ AL-QUR'AN ENVIRONMENT - Sholeh, Muh Ibnu; Mohamed, Mohamed Ramadan Abd Allah; Ali, Himad; Sokip; Syafi'i, Asrop; 'Azah, Nur (INTIHA: Islamic Education Journal, 2024)
This study aims to analyze the role of culture at Madrasah Aliyah Tahfidz Al-Qur'an Pesanggaran Banyuwangi in an effort to understand the cultural values in shaping student character and maintaining the sustainability of local culture. The research method used was qualitative by conducting in-depth interviews with school principals, teachers, administrative staff, and students. The interview results showed that the madrasa has a strong commitment to maintaining and strengthening cultural values in the educational environment, such as honesty, hard work, social awareness, and respect for local traditions. The main findings included the integration of cultural values in learning, the active role of all stakeholders in promoting cultural values, and students’ awareness of the importance of local culture The main challenge faced was the influence of globalization and technology which could divert students’ attention from local cultural values. Therefore, continuous efforts are needed to promote cultural values and increase students’ understanding and appreciation of local culture. This study contributes to an understandings of the role of culture in education and shows how an educational institution can become an agent for the maintenance and development of local culture.